2012
DOI: 10.1002/jnr.23084
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic modulation of low‐Mg2+‐induced epileptiform activity in the intact hippocampus of the newborn mouse in vitro

Abstract: To investigate whether epileptiform activity in the immature brain is modulated by dopamine, we examined the effects of dopaminergic agonists and antagonists in an intact in vitro preparation of the isolated corticohippocampal formation of immature (postnatal days 3 and 4) C57/Bl6 mice using field potential recordings from CA3. Epileptiform discharges were induced by a reduction of the extracellular Mg(2+) concentration to 0.2 mM. These experiments revealed that low concentrations of dopamine (<0.3 μM) attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Frontiers in Cell and Developmental Biology frontiersin.org contrary, D2R is coupled with Gi protein so that inactivation of D2R-MSN can be fulfilled through agonizing D2R. Controversial effects of dopaminergic agonists and antagonists applied in in vitro or systematic ways on seizures have been reported, but in most cases, it was reported that dopamine D1R agonists are proconvulsant and that D2R agonists are anticonvulsant (Wahnschaffe and Loscher, 1991;Starr, 1996;Sharopov et al, 2012;Brodovskaya and Kapur, 2021). In line with these previous studies showing D1R antagonists and D2R agonists are antiepileptic, our results of chemogenetic inhibition of either D1R-MSN or D2R-MSN in the NAc shell proves to be protective for the brain from more severe seizure insult.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Cell and Developmental Biology frontiersin.org contrary, D2R is coupled with Gi protein so that inactivation of D2R-MSN can be fulfilled through agonizing D2R. Controversial effects of dopaminergic agonists and antagonists applied in in vitro or systematic ways on seizures have been reported, but in most cases, it was reported that dopamine D1R agonists are proconvulsant and that D2R agonists are anticonvulsant (Wahnschaffe and Loscher, 1991;Starr, 1996;Sharopov et al, 2012;Brodovskaya and Kapur, 2021). In line with these previous studies showing D1R antagonists and D2R agonists are antiepileptic, our results of chemogenetic inhibition of either D1R-MSN or D2R-MSN in the NAc shell proves to be protective for the brain from more severe seizure insult.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has indicated that dopamine can aggravate epileptiform activity by decreasing the Mg 2+ concentration in the newborn mouse hippocampus in vitro. Furthermore, the induction of changes in the GABAergic and glutamatergic systems leads to increased neuron excitability and the involvement of these dysregulated systems in epileptogenesis [17]. Glutamate receptors, including AMPA receptors, are characterized by influencing the alternation of Ca 2+ concentrations, thus causing neuronal death and becoming involved in the epilepsy pathophysiology [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Rat hippocampal slices were prepared as previously reported [ 27 , 28 , 29 , 30 , 31 ]. All efforts were made to minimize the number of animals used and their suffering.…”
Section: Methodsmentioning
confidence: 99%